The outcome of a statewide audit of the quality of positive behaviour support plans. Issue 2 (3rd April 2018) - Wardale, Simon; Davis, Fiona; Vassos, Maria; Nankervis, Karen
ABSTRACT: Background Quality behaviour support plans (BSPs) are critical for achieving positive outcomes for people with intellectual disability who exhibit challenging behaviour. This study measured the quality of BSPs for technical accuracy and appropriate readability. Method Ten disability support organisations provided 139 BSPs for evaluation using the Behavior Support Plan Quality Evaluation (BSP-QE II; to assess technical accuracy) and Flesch readability scores (to assess readability). Results The mean BSP-QE II score ( M  = 6.53) classified the BSPs analysed as "weak." Of interest, the elements of the BSPs that were subject to specific statutory regulation displayed greater quality. The readability scores indicated that plans were written using language that may not be understandable to typical direct support staff. Conclusions Poor quality BSPs, or those too complex to be readily understood, may not be implemented fully. Statutory regulation positively influences BSP quality; however, a more detailed focus on training and quality assurance is indicated.